In vitro Ploidy Manipulation for Crop Improvement - Touchell, Darren H.; Palmer, Irene E.; Ranney, Thomas G. (Frontiers in Plant Science, 2020)
In vitro regeneration systems provide a powerful tool for manipulating ploidy to facilitate breeding and development of new crops. Polyploid induction can expand breeding opportunities, assist with the development of seedless triploid cultivars, enhance ornamental characteristics and environmental tolerances, increase biomass and restore fertility in wide hybrids. In vitro ploidy manipulation is commonly induced using antimitotic agents such as colchicine, oryzalin and trifluralin, while many other antimitotic agents have been relatively unexplored. Successful induction requires a synergistic pairing of efficient penetration of the antimitotic agent and may be dependent the length of exposure and concentrations of antimitotic agents, tissue types, and interactions with basal media and plant growth regulators. In vitro conditions vary among taxa and individual genera, species, and cultivars, often requiring unique treatments to maximize polyploid induction. In some taxa, the induction of polyploidy influences in vitro growth, development, and root formation. Here we provide an overview of mitotic inhibitors and their application for in vitro ploidy manipulation for plant breeding and crop improvement.